Avaliação do processo orçamentário como instrumento de controle interno para gestão das instituições eclesiásticas - Silva, Aidê de Jesus (2015)
Recognized as nonprofit entities, the Churches currently see in front of enormous challenges, all structure survives through donations, which enhances the need for efficient management. In order to corroborate the internal controls of these ecclesiastical institutions and broaden the discussion of management studies and church accounting, this study aimed to verify if the budget is used as an internal control tool for management of Dioceses and Archdioceses present in Brazil. For the research we used the method of survey data collection that allowed the interpretation of data obtained through cluster analysis, developed with IBM SPSS Statistics statistical software using the Two Step Cluster method. In addition, it was found in the survey the level of maturity of the budget process developed in these institutions. The survey results show that these institutions use the budget as an internal control instrument, however, it is important that standardization of the budget process to meet all the Dioceses and Archdioceses. And the level of maturity where are these institutions is the third level budget process comprising a defined process; however, with no sophisticated procedures, but with formalization of existing practices